The Civilization Choice Problem Of Ukraine In The Context Of The Ideals Of Ukrainian Philosophy - Скиба, І. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The article is devoted to the study of the problem of civilizational choice of Ukraine in the context of ideals of Ukrainian philosophy. The aim and tasks. The article aims at investigating the impact of society’s informatization on cultural and historical experience; identifying features of spiritual development in modern Ukraine; outlining the specific features of Ukrainian philosophy in the context of the problem of identification of modern Ukraine. Research methods. The methodology of the study was based on systematic, cultural, historical and socio-cultural methodological approaches in their dialectical interrelation. The combination of these approaches with methods of analysis and synthesis, analogy, comparative approach, principles of interconnection and development made it possible to carry out this research. Research results. The impact of society’s informatization on cultural and historical experience is investigated. The features of spiritual development in modern Ukraine are revealed. The specific features of Ukrainian philosophy in the context of the problem of modern Ukraine identification are outlined. Discussion. The discussion in detail deals with the "philosophy of heart" (H. Skovoroda, P. Yurkevich) as a main traditional direction of Ukrainian philosophical thought, which reflects the peculiarities of the Ukrainian worldview mentality, manifested in the emotionally-vivid forms of "cordocentrism", by combining enthusiastic prescriptions with the sensuous sphere, with the intention of covering limitless into the limited, and the absolute into the relative. Conclusion. The negative consequences of informatization significantly actualize the problem of identification and civilization choice of modern Ukraine, which contains such external and internal aspects: the problem of heterogeneity of Ukraine, the presence of different historical memory, the problem of internal integration, the problem of external integration, etc. The civilizational choice of Ukraine must be consistent with the cultural and historical experience of the Ukrainian people, which, in particular, manifests itself in the specificity of Ukrainian philosophy.